Metamorphism and zircon U–Pb dating of garnet amphibolite in the Baoyintu Group, Inner Mongolia - Yaping Chen; Chunjing Wei; Jinrui Zhang; Hang Chu (My University, 2015)
Garnet amphibolite in the Baoyintu Group, Inner Mongolia, is mainly composed of garnet, hornblende, plagioclase, quartz and minor rutile/ilmenite. Garnet occurs as porphyroblasts surrounded by plagioclase, forming typical ‘‘white-eye socket’’ texture. Garnet shows grossular content of 0.26–0.28 and pyrope of 0.11–0.13, without signiﬁcant zoning. Plagioclase is generally zoned with anorthite (An) increasing from core to rim. The P–T pseudosection calculated using THERMOCALC in the system MnNCKFMASHTO shows that the garnet amphibolite experienced a clockwise P–T path with a peak at *1.3 GPa/725 °C deﬁned from the minimum An content in plagioclase and maximum pyrope content in garnet, followed by an isothermal decompression. LA-ICP-MS zircon dating for the garnet amphibolite indicates metamorphic ages of 399 ± 6 Ma. The peak P–T condition corresponds to a thermal gradient of *18 °C/km, indicating typical medium-pressure type that commonly occurs in orogenic process with crustal thickening. We prefer to interpret this orogenic event to be a result of collision, following the closure of the Paleo-Asian Ocean before the early Devonian although there is a popular view that the Paleo-Asian Ocean may have lasted to the early Mesozoic.
Keywords: Amphibolite; P–T pseudosection; Zircon U–Pb dating; Baoyintu Group; Central Asian Orogenic Belt; Палеозой::Девонская; Paleozoic::Devonian